Modification of Al-11% Si Alloy with Cl - Based Modifier - Lipinski, Tomasz (Manufacturing Technology Journal, 2015)
The microstructure of an unmodified hypoeutectic Al-11%Si alloy comprises large primary α phase dendrites, eutectic β phase crystals and eutectic α phase. This composition is responsible for the alloy's low strength parameters, and it limits the extent of practical applications. The mechanical properties of hypoeutectic silumins can be improved through chemical modification as well as traditional or technological processing. Modification improves the mechanical properties of alloys through grain refinement. This study presents the results of modification of Al-11%Si alloy with chlorine base modifier (NaCl + CaCl + SrCl2). The influence of the analyzed modifiers on the mechanical properties (tensile strength, elongation and Brinell hardness) of the processed alloy was presented in graphs. The modification of a hypoeutectic Al-11%Si alloy improved the alloy's properties. The results of the tests indicate that the mechanical properties of the modified alloy are determined by differences compositions modifiers which are introduced to the alloy.
Keywords: Al-Si alloys; silumin; mechanical properties; modification; Cl